Indonesia's Legal Policy in Responding to China's Trade War Retaliation Against the United States Based on the Principle of Protectionism: Politik Hukum Indonesia dalam Menghadapi Retaliasi Perang Dagang China terhadap Amerika Serikat Berdasarkan Prinsip Proteksionisme - Rastuti, Tuti; Khoirudin, Andian Achya Dzikriyyah (Faculty of Law, Universitas Pasundan, 2025)
The trade war between the United States and China, driven by protectionist policies, has significantly disrupted global trade flows. For Indonesia, the conflict impacts exports, imports, and investment, while raising three critical: protecting domestic industries, maintaining neutral trade relations, and adhering to the principles of the World Trade Organization (WTO). Indonesia must formulate a balanced legal and trade strategy that upholds both national interests and international obligations. This study analyzes Indonesia’s legal-political response to China’s trade war retaliation against the United States, emphasizing the application of protectionist principles within the WTO framework. Employing normative legal research with statutory and conceptual approaches, the study draws on WTO agreements, national trade laws, and relevant case studies. The research findings indicate that Indonesia is able to maintain economic stability and promote peaceful relations with both conflicting countries through trade cooperation, while remaining compliant with the principles of the World Trade Organization (WTO). The